International, evidence-based consensus treatment guidelines for idiopathic multicentric Castleman disease - van Rhee, Frits; Voorhees, Peter; Dispenzieri, Angela; Fosså, Alexander; Srkalovic, Gordan; Ide, Makoto; Munshi, Nikhil; Schey, Stephen; Streetly, Matthew; Pierson, Sheila K; Partridge, Helen L; Mukherjee, Sudipto; et al. (Blood, 2018)
Castleman disease (CD) describes a group of heterogeneous hematologic disorders with characteristic histopathological features. CD can present with unicentric or multicentric (MCD) regions of lymph node enlargement. Some cases of MCD are caused by human herpesvirus-8 (HHV-8), whereas others are HHV-8-negative/idiopathic (iMCD). Treatment of iMCD is challenging, and outcomes can be poor because no uniform treatment guidelines exist, few systematic studies have been conducted, and no agreed upon response criteria have been described. The purpose of this paper is to establish consensus, evidence-based treatment guidelines based on the severity of iMCD to improve outcomes. An international Working Group of 42 experts from 10 countries was convened by the Castleman Disease Collaborative Network to establish consensus guidelines for the management of iMCD based on published literature, review of treatment effectiveness for 344 cases, and expert opinion. The anti-interleukin-6 monoclonal antibody siltuximab (or tocilizumab, if siltuximab is not available) with or without corticosteroids is the preferred first-line therapy for iMCD. In the most severe cases, adjuvant combination chemotherapy is recommended. Additional agents are recommended, tailored by disease severity, as second- and third-line therapies for treatment failures. Response criteria were formulated to facilitate the evaluation of treatment failure or success. These guidelines should help treating physicians to stratify patients based on disease severity in order to select the best available therapeutic option. An international registry for patients with CD (ACCELERATE, #NCT02817997) was established in October 2016 to collect patient outcomes to increase the evidence base for selection of therapies in the future.